New approach in cost structuring of high speed hard turning - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (Trans Tech Publications, Switzerland, 2011)
Cost structuring of new technology is a critical mission which needs to be developed systematically to get accurate cost estimation. In this research a new approach was proposed and developed for cost structuring a new process. Cost modeling roadmap was proposed to guide the development of genetic cost model by integrating different cost estimating methods and supporting the optimum solution by using statistical technique in modelling the cost in high speed hard turning, then by building logical relationship between the different effective variables through three levels of cost drivers; main drivers, process and technical drivers and final drivers. Finally a MATLAB model was developed for simulating the final cost drivers to study the effect of different parameters on the cost drivers.